What assessment knowledge and skills do initial teacher education programs address? A Western Canadian perspective - Poth, Cheryl-Anne (Alberta Journal of Educational Research, 2013)
Teacher education programs play a crucial role in preparing teachers for their future assessment roles and responsibilities, yet many beginning teachers feel unprepared to assess their students’ performances (Mertler, 2009). To address concerns related to the relevancy of pre-service assessment education, this study examined 57 syllabi from assessment courses offered by 14 Western Canadian teacher education programs. Content analysis revealed trends related to the scope and nature of assessment education in terms of intended learner outcomes, instructional topics, teaching mediums, and assessment strategies. Implications for informing how initial teacher education programs go about preparing pre-service teachers for their future assessment roles and responsibilities are discussed. Les programmes de formation des enseignants jouent un rôle critique dans la préparation des enseignants face à leurs rôles et responsabilités relativement à l’évaluation. Il demeure, par contre, que plusieurs enseignants débutants se sentent pris au dépourvu face à l’évaluation de la performance de leurs étudiants (Mertler, 2009). Afin d’aborder des préoccupations liées à la pertinence de la formation à l’évaluation, cette étude a examiné 57 programmes de cours d’évaluation offerts dans le cadre de 14 programmes de formation des enseignants dans l’Ouest canadien. Une analyse du contenu a révélé des tendances liées à l’envergure et à la nature de l’éducation à l’évaluation, et portant sur les résultats d’apprentissage, les thèmes étudiés, les moyens d’enseignement et les stratégies d’évaluation. On discute des incidences de faire comprendre la préparation des enseignants face à leurs rôles et responsabilités relativement à l’évaluation.